(Process Quality Upgrading and Better Utilization of Java Citronella Oil) - Salya Sait; enny Hawani Lubis; Tiurlan Farida Hutajulu; Subagja - (Warta Industri Hasil Pertanian, 1997)
To obtain the good quality of International Market Standard and better oil as raw material for rose oil synthetic where as the price of natural rose oil is much higher in price that of synthetic. The fractional distillation process was employed on crude Java Citronella oil grown in Sukabumi and Purwokerto to obtained the oil with international market quality and the oil fraction was used as basic material for rose oil synthesis. It was concluded that due to a high cost of the fractional distillation, it was unable to raise the economic added value of crude oil via quality improvement using this process except when the oil fraction was used as basic material for rose oil synthesis.